Luminescent Eu3+ doped Al6Ge2O13 crystalline compounds obtained by the sol gel process for photonics - Maia, Lauro J.Q.; Faria Filho, Fausto M.; Gonçalves, Rogéria R.; Ribeiro, Sidney J.L. [UNESP] (Elsevier, 2018)
We synthesized pure and Eu3+ doped Al6Ge2O13 samples by an easy and low-cost sol-gel route using the GeO2, Al(NO3)3·9H2O and Eu(NO3)3·6H2O as precursors, tetramethylammonium hydroxide and ethanol as solvents. The Al6Ge2O13 crystalline phase possesses orthorhombic structure and is a potential host for rare earth ions, especially due to high aluminum concentration. Homogeneous and transparent sols and gels were obtained. The samples containing 1 mol% of Eu3+ were heat-treated at 1000 °C to eliminate organic compounds, providing high optical quality and structural purity. All materials were characterized by thermogravimetric and differential thermal analysis, X-ray diffraction, Fourier transform infrared spectroscopy, high resolution transmission electron microscopy, selected area electron diffraction, diffuse reflectance spectra in the ultraviolet–visible–near infrared regions and photoluminescence measurements. High purity of Eu3+ doped Al6Ge2O13 orthorhombic phase and well crystallized grain dimensions of around 100 nm was obtained with high red photoluminescence emission. The decay lifetime of 5D0 level from Eu3+ (the emission at 612 nm) was determined, being between 0.97 and 2.12 ms, and an average quantum efficiency of 54% was determined (considering the average experimental lifetime of 1.77 ms). Moreover, it was calculated and analyzed some parameters of Judd-Ofelt theory applied to Eu3+ emissions from Al6Ge2O13 host. The results show that Eu3+ doped Al6Ge2O13 crystalline compounds have large potential to be used in displays and LED devices.
Keywords: Al6Ge2O13 crystalline phase; Eu3+ doped; Optical properties; Structural properties